KONSELOR IDEAL DALAM BUDAYA NGERENG DHABU DI MADURA - Fadlilah, Fadlilah (JURNAL SETIA PANCASILA, 2021)
The socio-cultural life of the Madurese community is full of the inheritance of the local wisdom of the people, at least we can see in the culture of Ngereng Dhabu. The value of Ngereng Dhabu in another approach can be said to be a form of devotion to figures such as a Kiai or people who are socially more respected in their environment. Hierarchically, it is like a Madurese philosophy of Bhuppa'-Bhabhu'-Ghuru-Rato, and the value of keihklashan in the cultural concept of Ngereng Dhabu is a construction of the collective life of the Madurese community whose historicity lasts relatively long. The Madurese hierarchically obey these figures, and the culture of Ngereng Dhaba is a form of ethical behavior in a community called local wisdom, as they reconstruct the conception of devotion and obedience in their social life. does not reflect the values ??of devotion and sincerity implied in the concept of Ngereng Dhabu Culture. Ideally, the character of a counselor must have a high sense of dedication and great sincerity in carrying out the service process, in order to help others in overcoming problems faced by the counselee.